2013
DOI: 10.1149/2.003306jes
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Nanostructured Ag Films on Silicon Wafers by Electrochemical/Electrophoretic Deposition for Electrochemical and SERS Sensing

Abstract: Electrolysis of ultrapure water in a two-electrode cell with silver anode and conductive substrate (Si wafer) as a cathode leads to the formation of nanostructured silver layers deposited on cathode. In the process, the silver anode is electrochemically dissolved to silver cations, which react with water (or OH • radicals derived from water electrolysis) forming silver oxide nanoparticles, which fill the interelectrode space by electrophoretic movement, diffusion and convection induced by temperature effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Despite the fact that Ag NPs preparation methods based on the reduction of insoluble silver salts are not as widely examined as is the reduction of soluble silver salts, insoluble silver salt reduction methods could pose some advantages such as simple preparation of thin films or composites because of better affinity of silver compounds to the carrier compared to metallic silver [ 57 59 ]. Also, preparation of stable nanoparticles with very small diameters is feasible using this method [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that Ag NPs preparation methods based on the reduction of insoluble silver salts are not as widely examined as is the reduction of soluble silver salts, insoluble silver salt reduction methods could pose some advantages such as simple preparation of thin films or composites because of better affinity of silver compounds to the carrier compared to metallic silver [ 57 59 ]. Also, preparation of stable nanoparticles with very small diameters is feasible using this method [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure for CFME modication by copper is based on a methodology 15 previously described by ourselves for the preparation of nanostructured silver layers, i.e. electrodeposition of the material formed by the dissolution of the anode.…”
Section: Preparation Of Copper-coated Carbon Fiber Microelectrodementioning
confidence: 99%
“…[8][9][10][11][12] In our previous works, we have reported that carbon ber microelectrodes (CFMEs) can be utilized as highly sensitive electrochemical detectors, especially in HPLC. [13][14][15][16] Thereby, we developed a facile technique enabling CFMEs to be modied with nanostructured copper layers. The dimensions of a carbon ber (3-4 mm in length, 7 mm in diameter) enable the direct insertion of the active electrode tip into a narrow-bore capillary even aer the modication with copper.…”
mentioning
confidence: 99%
“…The sensitivity of conventional Raman scattering is inherently low due to the fact that only a small fraction of photons is used for detection (inelastically scattered photons) leading to very small cross sections of the order of 10–30 cm 2 /sr [ 8 ]. This intrinsic limitation can be overcome by the use of rough and/or nanostructured substrates covered by coinage metals, mainly silver and/or gold nanoparticles, or copper, which provide significant enhancement factors of the order of 10 4 –10 7 as a result of the excitation of localized surface plasmons [ 9 , 10 , 11 ]. SERS can take place near a metallic nanoparticle, which is irradiated at the resonance frequency or near resonance of its localized surface plasmons resulting in a large enhancement of both the local and radiation fields in the vicinity of the metallic nanoparticles and thus in a marked amplification of the Raman signal from adsorbed molecules [ 12 ].…”
Section: Introductionmentioning
confidence: 99%